A study of the vocabulary learning strategies of English 10 students - Tuplano, Monnette Israel; Salonga, Aileen O. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
This is a study of the vocabulary learning strategies of students in five English 10 classes. This study aims to connect the use of strategies to the success of the students in their learning process, particularly in vocabulary building. A vocabulary test and a strategy questionnaire are administered to gauge the vocabulary levels of the students and to find out what vocabulary learning strategies the students use and how often.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: English language -- Glossaries, vocabularies, etc